2022
DOI: 10.1108/tqm-10-2021-0291
|View full text |Cite
|
Sign up to set email alerts
|

The implementation of Lean Six Sigma framework in the Indian context: a review and suggestions for future research

Abstract: PurposeThe purpose of this work is to gain insights about Lean Six Sigma (LSS) in the Indian context by reviewing the related literature for one decade based on various perspectives, such as author profile, year of publication, type of firm, type of methodology used, type of industry for which the research work is carried out and the key findings from the research.Design/methodology/approachThis study reviews the research related to LSS from the articles published in the reputed journals. The literature used f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 126 publications
0
14
0
Order By: Relevance
“…Based on the research gap identified from the literature and the recommendations and suggestions given by various authors in this field and by conducting a systematic literature review using appropriate keywords in reputable sources like WoS, Google Scholar, Scopus, Taylor and Francis, Inderscience, Emerald Insights and others, a conceptual framework was developed that emphasizes the ergonomics, sustainability and operational impact of LSS 4.0. To locate the pertinent papers for the conceptual framework of LSS 4.0, the forward and backward snowballing approaches, as well as a specific journal search approach, were utilized in addition to the systematic literature review (Tranfield et al, 2003;Yadav and Desai, 2016;Citybabu and Yamini, 2022). Research methodology adopted for this study IJPPM 73,5…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Based on the research gap identified from the literature and the recommendations and suggestions given by various authors in this field and by conducting a systematic literature review using appropriate keywords in reputable sources like WoS, Google Scholar, Scopus, Taylor and Francis, Inderscience, Emerald Insights and others, a conceptual framework was developed that emphasizes the ergonomics, sustainability and operational impact of LSS 4.0. To locate the pertinent papers for the conceptual framework of LSS 4.0, the forward and backward snowballing approaches, as well as a specific journal search approach, were utilized in addition to the systematic literature review (Tranfield et al, 2003;Yadav and Desai, 2016;Citybabu and Yamini, 2022). Research methodology adopted for this study IJPPM 73,5…”
Section: Methodsmentioning
confidence: 99%
“…To locate the pertinent papers for the conceptual framework of LSS 4.0, the forward and backward snowballing approaches, as well as a specific journal search approach, were utilized in addition to the systematic literature review (Tranfield et al. , 2003; Yadav and Desai, 2016; Citybabu and Yamini, 2022).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…To ensure improved regulatory compliance, Jalundhwala and Londhe (2023) identified a number of enablers for operational excellence in the pharmaceutical sector. Some evidence of lean practices in different regions can be found in many publications such as (Garza-Reyes et al, 2012;Ghosh, 2013;Krishnan et al, 2022;Verma et al, 2022;Citybabu and Yamini, 2022;Hasan et al, 2022).…”
Section: Introductionmentioning
confidence: 99%